Moderation Of The Internal Control System On Factors Influencing The Quality Of Regional Financial Reporting - Novita Sari; Fadli Fadli; Herawansyah Herawansyah; Vika Fitranita (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study examines the Influence of Government Accounting Standards, SIMDA Implementation, and Human Resource Quality on the quality of local government financial reports, taking into account the moderating effect of the internal control system. It was conducted in 34 Regional Work Units (SKPD) in the Bengkulu province with 99 respondents. The results indicate that government accounting standards, SIMDA Implementation, and Human Resource Quality do not have a significant impact on the quality of local government financial reports. The internal control system does not moderate the impact of government accounting standards, but it does moderate the influence of SIMDA implementation and human resource quality on the quality of financial reports. There are limitations in the research sample due to some SKPD having employees who do not meet the research criteria.